ANALISIS PROSES PEMBELAJARAN IPA PADA MATERI CAHAYA MELALUI LESSON STUDY BERBASIS TBLA (TRANSCRIPT BASED LESSON ANALYSIS) DI KELAS VIII.2 SMP ISLAM Al-FALAH KOTA JAMBI - Nova Susanti; Melisa Murzanita; Neneng Lestari (Universitas Jember, 2021)
This study analyzes the science learning process through a TBLA-based lesson study (Transcript Based Lesson Analysis), where the analysis is focused on the teacher-centered and student-centered. There are stages of lesson study that are implemented, namely planning (plan), implementation (do), and reflection (see). This study uses a qualitative approach with a case study research type. This research was carried out in class VIII.2 of Al-Falah Islamic Junior High School in Jambi City from January 18 to February 22, 2021, through 2 research cycles. This study's data source was 32 students of class VIII.2, with details of 20 male students and 12 female students. Qualitative data were obtained through observation and documentation. Observers make statements during the learning process. At the same time, documentation is received from audio/video recordings of the learning process (interactions between teachers and students), which will then be transcribed in learning dialogue. The results obtained are based on the transcript of the conversation, which is made in a word unit graphic. It can be seen that the science learning process in cycle one and cycle two is still dominated by teachers or is teacher-centered. The teacher has allowed students to speak with existing questions and group discussions. The suggestion in this research is that teachers can apply TBLA-based lesson study in the learning process. Analytical techniques like this aim to improve the ability of teachers to enhance further learning processes.